Oxygen evolution reaction electrocatalysts for efficient hydrogen production in anion exchange membrane water electrolyzers - Chen, Di (Kansas State University, 2023)
Due to the global energy crisis and climate change, developing clean energy sources, such as hydrogen, is becoming urgent. A critical method for hydrogen production is electrochemical water splitting (i.e., water electrolysis), specifically through anion exchange membrane water electrolyzers (AEMWEs), which combine the advantages of both alkaline water electrolyzers (AWEs) and proton exchange membrane water electrolyzers (PEMWEs). AEMWEs with excellent fabrication are a vital way in pursuit of efficient and environmentally hydrogen generation. However, AEMWEs suffer from low energy efficiency and poor hydrogen production rate, which is ascribed to the sluggish kinetics of the anodic oxygen evolution reaction (OER) in the alkaline media. Therefore, it is crucial to discover an efficient catalyst to increase the reaction rate. Highly active and platinum group metal-free (PGMfree) OER electrocatalysts are essential for producing low-cost and clean hydrogen in AEMWEs. Thanks to the unique characteristics of perovskite oxides, oxyhydroxide (OOH), and layered double hydroxides (LDH), which include low-cost, tunable electronic structure and cation deficiency, high electronic conductivity, high durability, high specific catalytic activity, and environmental friendliness, they are widely designed and employed as the OER electrocatalysts. This study centers on designing, synthesizing, and characterizing new OER electrocatalysts, including perovskite oxides, oxyhydroxide (OOH), and layered double hydroxides (LDH), which aims to produce green hydrogen in AEMWEs with enhanced energy efficiency. Ruddlesden–Popper perovskite is one type of perovskite group and also a great OER electrocatalyst. Here, a set of novel hybrid perovskites, La[subscript x]Sr[subscript 4-x]Ni[subscript y]Fe[subscript 3-y]O[subscript 10-[delta]] (L[subscript x]S[subscript 4-x]N[subscript y]F[subscript 3-y]), were demonstrated, which consist of a single-layer perovskite phase (P phase) and two Ruddlesden–Popper perovskite phases (RP phases). These hybrid perovskites synergize the advantages of the P phase and RP phases, which improves the oxygenion diffusion rate, leading to enhanced OER activity. Furthermore, the concentration of each phase can be tuned by alternating the compositional stoichiometry. A relatively uniform distribution of the P phase and RP phases can maximize the interfacial area and achieve the highest oxygen-ion diffusion rate. L₃S₁N₂F₁, L₂S₂N₁F₂, and L₂S₂N₁.₅F₁.₅ exhibit outstanding OER activity, which achieve 10 mA/cm² at a low overpotential of <360 mV in 1.0M KOH. Additionally, herein, the hybrid perovskites are implemented as the anodes of AEMWEs, which deliver an exceptional current density of >1.0 A/cm² at 1.8V. Additionally, we demonstrate unique perovskite oxides, La[subscript x]Ce[subscript 1-x]Ni[subscript y]Fe[subscript 1-y]O[subscript 3-[delta] (L[subscript x]C[subscript 1-x]N[subscript y]F[subscript 1-y]). L[subscript 0.9]C[subscript 0.1]N[subscript 0.7]F[subscript 0.3] exhibits outstanding OER activity, which achieves 10mA/cm² at a low overpotential of 338mV in 1.0 M KOH in a half-cell test. Furthermore, L[subscript 0.9]C[subscript 0.1]N[subscript 0.7]F[subscript 0.3] and L[subscript 0.9]C[subscript 0.1]N[subscript 1] show the unique feature that the performance tends to increase at the beginning of the stability test. Moreover, oxyhydroxide (OOH) is also a type of platinum group metal-free (PGMfree) electrocatalysts for oxygen evolution reaction (OER) electrodes in AEMWE, which displays excellent performance. In this study, the OOH electrode is different from perovskite oxides, L[subscript x]C[subscript 1-x]N[subscript y]F[subscript 1-y], hybrid RP-perovskite electrode, and L[subscript x]S[subscript 4-x]N[subscript y]F[subscript 3-y]. Ni-incorporated CoFeOOH on Fe foam (NiCoFeOOH/FF) is a 3-D unified electrode without a binder. Herein, first, we optimize cobalt–iron (oxy)hydroxide (CoFeOOH/FF), which is directly grown on Fe foam via the galvanic corrosion method, with different Co concentrations to achieve great catalyst activity for OER. Then, Ni-incorporated CoFeOOH on Fe foam (NiCoFeOOH/FF) with different Ni concentrations is prepared. CoNiFeOOH with a Co/Ni ratio of 20:10 (NiCoFeOOH/FF 10) exhibits outstanding OER activity, which achieves superior catalytic performance. At a current density of 10 mA/cm², a low overpotential of 234 mV is achieved in 1.0 M KOH at room temperature in half-cell testing. Additionally, NiCoFeOOH/FF 10 is implemented as the anode of AEMWE full cells, which delivers an exceptional current density of 1.6 A/cm² at 1.8V and 50℃. This study shows a new insight into designing OER catalysts in water splitting. Furthermore, unlike the above water splitting utilizing pure water, this research also explores seawater electrolysis. As an abundant and more environmentally conscientious alternative resource, seawater could be used directly in electrochemical water splitting to generate hydrogen, which is also helpful for seawater desalination. In seawater electrolysis, it is imperative to utilize electrocatalysts that exhibit exceptional activity for the oxygen evolution reaction (OER) and catalyst selectivity. NiFe LDH is one type of advanced OER electrode in water electrolysis. This thesis investigated the highly active electrocatalyst NiFe LDH with different Ni/Fe ratios half-cell test scale. NiFe LDH with Ni/Fe ratio 75/25 (NiFe LDH 75) expressed outstanding performance, with an overpotential of 282 mV at a current density of 10mA/cm². In simulated seawater, an overpotential of 378 mV is achieved at a current density of 10 mA/cm², which is higher than that attained in 1M KOH. However, the performance is much better than the previous report catalyst, for example, IrO₂. Additionally, NiFe LDH 75 is studied as the OER electrode of AEMWEs with different configurations for seawater electrolysis. All asymmetric feeds expressed remarkable performance, achieving an exceptional current density of >1 A/cm² at 1.8 V, and a high Faradaic efficiency, close to 100%. Feeding 1M KOH to the anode and 0.5M NaCl to the cathode, an energy conversion efficiency of 77% is achieved, and long-time stability in seawater was demonstrated up to 150 hours. Our NiFe LDH 75 AEM catalyst operated in simulated seawater demonstrated superior performance compared to the previously reported AEM electrolyzer performed in 1.0 M KOH. In summary, this comprehensive investigation navigates through diverse OER electrocatalytic materials, L[subscript 0.9]C[subscript 0.1]N[subscript 0.7]F[subscript 0.3], L₃S₁N₂F₁, NiCoFeOOH/FF 10, and NiFe LDH 75, unveiling innovative pathways to enhance energy efficiency and achieve sustainable hydrogen production through electrochemical water splitting and seawater electrolysis in the backdrop of a rapidly evolving energy landscape
Keywords: Anion exchange membrane water electrolyzers; Perovskite oxides; Hydrogen production; NiFe LDH; CoFeOOH